The assessment of interhemispheric imbalance using functional near-infrared spectroscopic and transcranial magnetic stimulation for predicting motor outcome after stroke - Chen, Songmei; Zhang, Xiaolin; Chen, Xixi; Zhou, Zhiqing; Cong, Weiqin; Chong, KaYee; Xu, Qing; Wu, Jiali; Li, Zhaoyuan; Lin, Wanlong; Shan, Chunlei (Frontiers in Neuroscience, 2023)
Objective To investigate changes in interhemispheric imbalance of cortical excitability during motor recovery after stroke and to clarify the relationship between motor function recovery and alterations in interhemispheric imbalance, with the aim to establish more effective neuromodulation strategies. Methods Thirty-one patients underwent assessments of resting motor threshold (RMT) using transcranial magnetic stimulation (TMS); the cortical activity of the primary motor cortex (M1), premotor cortex (PMC), and supplementary motor area (SMA) using functional near-infrared spectroscopy (fNIRS); as well as motor function using upper extremity Fugl-Meyer (FMA-UE). The laterality index (LI) of RMT and fNIRS were also calculated. All indicators were measured at baseline(T1) and 1 month later(T2). Correlations between motor function outcome and TMS and fNIRS metrics at baseline were analyzed using bivariate correlation. Results All the motor function (FMA-UE1, FMA-UE2, FMA-d2) and LI-RMT (LI-RMT1 and LI-RMT2) had a moderate negative correlation. The higher the corticospinal excitability of the affected hemisphere, the better the motor outcome of the upper extremity, especially in the distal upper extremity (r = −0.366, p = 0.043; r = −0.393, p = 0.029). The greater the activation of the SMA of the unaffected hemisphere, the better the motor outcome, especially in the distal upper extremity (r = −0.356, p = 0.049; r = −0.367, p = 0.042). There was a significant moderate positive correlation observed between LI-RMT2 and LI-SMA1 (r = 0.422, p = 0.018). The improvement in motor function was most significant when both LI-RMT1 and LI-SMA1 were lower. Besides, in patients dominated by unaffected hemisphere corticospinal excitability during motor recovery, LI-(M1 + SMA + PMC)2 exhibited a significant moderate positive association with the proximal upper extremity function 1 month later (r = 0.642, p = 0.007). Conclusion The combination of both TMS and fNIRS can infer the prognosis of motor function to some extent. Which can infer the role of both hemispheres in recovery and may contribute to the development of effective individualized neuromodulation strategies.